Implementasi Metode Low Poly Pada Animasi 3D “Serendipity” Dengan Teknik Animasi - Sethyani Kadang Allo; Muchamad Zainul Rohman; Damar Nurcahyono (JURNAL VOKASI TEKNIK, 2024)
The process of creating 3D animation has experienced rapid development through creative innovations and computer technology. Animated films, particularly those based on 3D, have become popular across various age groups. Low poly modeling was the focus in the production of the animation 'Serendipity.' This research employs the Multimedia Development Life Cycle (MDLC) method with the goal of providing practical references for 3D model creation. The research object references the modeling of Bebaya Park in Samarinda City. The animated video was successfully created by applying low poly techniques to the modeling of Bebaya Park. Testing was conducted with 5 respondents, and the results indicated that the low poly approach used was appropriate.